Performance of the Genomic Evaluators of Metastatic Prostate Cancer (GEMCaP) Tumor Biomarker for Identifying Recurrent Disease in African American Patients - Levin, Albert M.; Lindquist, Karla J.; Avila, Andrew; Witte, John S.; Paris, Pamela L.; Rybicki, Benjamin A. (Cancer epidemiology, biomarkers & prevention, 2014)
Evaluation of prostate cancer prognosis after surgery is increasingly relying upon genomic analyses of tumor DNA. We assessed the ability of the biomarker panel Genomic Evaluators of Metastatic Prostate Cancer (GEMCaP) to predict biochemical recurrence in 33 European American and 28 African American prostate cancer cases using genome-wide copy number data from a previous study. “Biomarker positive” was defined as ≥20% of the 38 constituent copy number gain/loss GEMCaP loci affected in a given tumor; based on this threshold, the frequency of a positive biomarker was significantly lower in African Americans (n = 2; 7%) than European Americans (n = 11; 33%; P = 0.013). GEMCaP positivity was associated with risk of recurrence [hazard ratio (HR), 5.92; 95% confidence interval (CI), 2.32–15.11; P = 3 × 10−4] in the full sample and among European Americans (HR, 3.45; 95% CI, 1.13–10.51; P = 0.032) but was not estimable in African Americans due to the low rate of GEMCaP positivity. Overall, the GEMCaP recurrence positive predictive value (PPV) was 85%; in African Americans, PPV was 100%. When we expanded the definition of loss to include copy-neutral loss of heterozygosity (i.e., loss of one allele with concomitant duplication of the other), recurrence PPV was 83% for European American subjects. Under this definition, 5 African American subjects had a positive GEMCaP test value; 4 went on to develop biochemical recurrence (PPV = 80%). Our results suggest that the GEMCaP biomarker set could be an effective predictor for both European American and African American men diagnosed with localized prostate cancer who may benefit from immediate aggressive therapy after radical prostatectomy. Cancer Epidemiol Biomarkers Prev; 23(8); 1677–82. ©2014 AACR.